Effects of 12‐Week Moderate‐Intensity Versus High‐Intensity Water‐Aerobic Training on Physical Fitness, Cardiovascular Health, and Well‐Being in Adults and Older Adults: A Pragmatic Randomized Controlled Trial - Luís Brandão Faíl; Daniel Almeida Marinho; Elisa A Marques; Juliana Mendes Gonçalves; Maria Helena Gil; Rogério Alves Pereira; Mário Cardoso Marques; Mikel Izquierdo; Henrique Pereira Neiva (Health Science Reports, 2024)
ABSTRACT Background and Aims The current study aimed to compare the effects of 12 weeks of moderate versus high‐intensity water aerobics on muscle strength, body composition, lipid profile, blood pressure, and quality of life in both adults and older adults. Methods Twenty‐one women (65.19 ± 9.37 years) were randomly allocated to moderate (MIG; n = 11) or high‐intensity groups (HIG; n = 10). Both groups attended 45‐min sessions twice a week for 12 weeks. Assessments at baseline and posttraining included muscle endurance, explosive strength, body mass, body mass index, fat mass, fat‐free mass, triglycerides, total cholesterol, blood pressure, resting heart rate, general quality of life, and general health, and the physical, psychological, social relationships, and environmental domains of quality of life. Results HIG experienced greater reductions in cholesterol (ηp2 = 0.28) and fat mass (ηp2 = 0.35), and an increase in fat‐free mass (ηp2 = 0.35), compared to the MIG. The HIG also showed greater improvements in triglycerides (ηp2 = 0.24) and physical quality of life (ηp2 = 0.19) than MIG. No significant group × time interactions were found in the other variables. Nevertheless, muscular endurance and psychological quality of life were improved in both groups (p < 0.05, ES ≥ 0.57). The HIG was the only group to experience a reduction in diastolic blood pressure (p = 0.04, ES = −0.71), while the MIG showed no significant change. Explosive strength did not change in either group. Conclusion The study suggests that high‐intensity water aerobics provide additional benefits over moderate intensity for body composition, blood lipids, diastolic blood pressure, and physical quality of life in adults and older adults. However, both intensities effectively improved muscular endurance and psychological quality of life. Future studies should include a larger number of participants and groups (e.g., control group), longer interventions, and controlled dietary intake. Nonetheless, the current results demonstrate that exercise intensity is an important variable for optimal water aerobics outcomes.